2021
DOI: 10.21037/tlcr-21-898
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted thoracic surgery reduces perioperative complications and achieves a similar long-term survival profile as posterolateral thoracotomy in clinical N2 stage non-small cell lung cancer patients: a multicenter, randomized, controlled trial

Abstract: Background: Our previous study demonstrated the safety and short-term efficacy of robotic-assisted thoracic surgery (RATS) in clinical N2 (c-N2) stage non-small cell lung cancer (NSCLC) patients. From this, the present study was devised, in which the follow-up time and sample size were both extended to explore the long-term efficacy and potential benefit in survival of RATS compared with lobectomy in c-N2 stage NSCLC patients.Methods: Patients with c-N2 NSCLS were randomly assigned in a 1:1 ratio to accept ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…we did not observe any difference in the duration of epidural tube use. Although many studies reported that RATS showed a more favorable pain control profile compared with thoracotomy, there were no significant difference between RATS and VATS (21,22).…”
Section: Discussionmentioning
confidence: 86%
“…we did not observe any difference in the duration of epidural tube use. Although many studies reported that RATS showed a more favorable pain control profile compared with thoracotomy, there were no significant difference between RATS and VATS (21,22).…”
Section: Discussionmentioning
confidence: 86%
“…The best surgical option for resectable stage II and above NSCLC is still controversial, and studies generally agree that thoracotomy can achieve excellent long-term postoperative outcomes, especially in lymph node dissection (13,19). It has been reported recently that RATS has the same long-term outcomes as thoracotomy and VATS, as well as better short-term results (20)(21)(22)(23)(24). The ROMAN study (7) and RVlob Trial (25), which is a perioperative randomized multicentric clinical trial for stage I-II NSCLC, both confirmed that robotic methods can improve lymph node staging and obtain a higher lymph node yield.…”
Section: Discussionmentioning
confidence: 99%
“…Following review of the title and abstract, 863 studies were excluded and a full text review was performed on the remaining 47 articles. Twenty-two studies reporting on a total of 104,472 patients who underwent either RVATS ( n = 12,061) or open thoracotomy ( n = 92,411) lung resection met the selection criteria [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A summary of the study selection process is shown in Figure 1 as a PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent network meta-analysis of 34 studies of 183,426 patients by Aiolfi [ 3 ] showed significantly reduced 30-day mortality, pulmonary and overall complications, as well as equivocal oncological and five-year survival outcomes in RVATS compared to VATS and open thoracotomy. However, a multicenter randomized controlled trial by Huang [ 11 ], comparing RVATS with open thoracotomy in 148 patients with N2 NSCLC, reported only significant reductions in blood loss, pain and chest drain duration in the RVATS group, but no difference in the other postoperative outcomes. In contrast to the previous studies, this present meta-analysis has shown a significant reduction in atrial arrhythmia and a significant increase in the number of lymph nodes stations harvested in the RVATS group compared to open thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation